Investors Sentiments and Firm Financial Leverage: An Examination of Market Timing and Debt Capacity Theories - Mohammad Jalili; Valiyollah Khosravi; Mohammad Mahdi Momenzadeh; Sajad Gorjizadeh (راهبرد مدیریت مالی)
The argument of the market timing theory assumes that when the valuation is overvalued, the issuance of new shares prevents the issuance of debt and financial leverage. On the contrary, the argument of the debt capacity theory assumes that the tendency to increase the future cash flows of frims that leads to debt issuance and financial leverage. Therefore, the purpose of this research is to investigate the relationship between investors sentiments and the frims financial leverage. The financial information of 167 frims admitted to the Tehran Stock Exchange during the years 2013 to 2022 were used to test the hypotheses. Also, to test the research hypotheses, multivariate regression analysis and Eviews econometric software and statistical techniques of panel data were used with the control of year and industry effects after measuring the research variables. The findings of the research indicate that according to the prediction of market timing theory, there is a negative and significant relationship between investors sentiments and the frims financial leverage. These results show that standard setters, legislators and experts should pay more attention to the psychological factors of investors to identify investors sentiments. Finally, in this research, it leads to a greater understanding of the users of the impact of investors sentiments on making financing decisions of business units.